Implementasi Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah pada Pembelajaran IPS Siswa Kelas V Sekolah Dasar - Bunga Cinta Ananda Rusman; Mohammad Syarif Sumantri; Linda Zakiah (Departement of Mathematics Education, 2023)
This study aims to determine the process of applying the problem-based learning model to improve problem-solving skills in social studies learning about problems that occur in the environment around fifth grade elementary school students. The method used in this research is descriptive qualitative method. This research was conducted at SDN Kampung Bulak 03, Pamulang District, South Tangerang City. The subjects in this study were all students of class V B at SDN Kampung Bulak 03 with a total of 27 students. With a total of 12 male students and 15 female students. Data collection techniques used in this study were interviews, observation, and documentation. The results showed that the problem-based learning model could improve problem-solving skills in social studies learning for fifth grade elementary school students. And the teacher succeeded in applying the problem-based learning model according to the syntax or learning steps. This can be seen from the enthusiasm and activeness of students in solving problems in learning activities.